Penyuluhan Brain Gym Pada Penderita Pasca Stroke Iskemik di Desa Candirejo - manik, maria hermita; Alwi, Fahrizal; Rosaulina, Meta; Marlina, Siti; Hasian, Muhammad Tsawaby; Tarigan, Beti Susanti (INSTITUT KESEHATAN DELI HUSADA, 2025)
Ischemic stroke is one of the main causes of disability in the elderly group which has an impact on decreased motor and cognitive function. The post-stroke recovery process requires non-pharmacological interventions that can be done independently at home with family support. Brain Gym or brain gymnastics is a simple method that has been proven to stimulate the integration of brain and body functions, as well as improve balance, coordination, and concentration. This community service activity aims to improve the knowledge and skills of post-ischemic stroke sufferers and their families in implementing Brain Gym as part of independent rehabilitation efforts. The implementation method includes providing education through interactive lectures, demonstrations of Brain Gym movements, and direct practice sessions guided by the implementation team. The activity was carried out in Candirejo Village, Semarang Regency, involving 25 participants consisting of stroke survivors, family members, and health cadres. The eval_uation was carried out using a pre-test and post-test which showed an increase in participants' knowledge scores by 35%. The results of the activity showed that Brain Gym counseling was effective in increasing participants' understanding and motivation to do routine exercises at home. This activity is expected to support the rehabilitation process and improve the quality of life of post-stroke sufferers in a sustainable manner.